Analisis Kualitas Fasilitas Ruang Kelas dan Dampaknya Terhadap Proses Pembelajaran Di Sekolah Dasar - Elvi Mailani; Nurhudayah Manjani; Delfi Wulandari; Riani Tazkia Hadi; Safana Nur Rizky; Lidwina Roulina Turnip; Nazwa Dewi Tianda (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to analyze the lack of classroom facilities and its impact on the learning process in elementary schools. The data source for this research was taken from an iterative study and observations carried out in one of the schools, namely Attaufiq Elementary School, Medan. This research was carried out by observing first, then the research team looked for relevant research data sources from books, journals, documents and other written works, then carried out data analysis to obtain data that was relevant to the topic being researched, so as to be able to achieve the research objectives. The final stage is preparation, each source and research result is arranged systematically and structured, starting from the introduction, research methods, research results, conclusions and bibliography. With this study, it is hoped that it can provide an overview for school residents who experience the problem of lack of school facilities to be more innovative and creative in designing other alternative solutions or using alternative solutions offered to overcome and improve the learning process.